Sultan Ground: Dialektika Pluralisme Hukum Dalam Pengelolaan Hukum Pertanahan Nasional - Gautama, Tirta; Firdaus F, M Waritsul; Taufiq, M Shofwan (Universitas Muhammadiyah Metro, 2024)
Law No. 13 of 2012 on the Special Status of Yogyakarta grants special authority to the Special Region of Yogyakarta (DIY), including in land management by the Sultanate of Ngayogyakarta Hadiningrat and the Kadipaten Puro Pakualaman. The history of land ownership by the Sultanate and the Kadipaten, recognized since the colonial era through the Rijksblad of the Sultanate No. 16 of 1918 and the Rijksblad of Pakualaman No. 18 of 1918, demonstrates a clash between national agrarian law and DIY’s traditional laws. This legal dualism creates conflicts and legal uncertainties related to land ownership in Yogyakarta.This paper explores the legal dialectic in the management of Sultan Ground in Yogyakarta, analyzing the legal pluralism resulting from the layered authority system between the central and regional governments, as well as the politics of traditionalism post-reformation. The ongoing political and agrarian law changes reflect efforts to balance local and national interests in land management, particularly in special regions like Yogyakarta